Rapid Surgery. - Baker, Cara R. (John Wiley & Sons, 2011)
This pocket reference and revision guide is a must for all medical students and junior doctors preparing for major surgical exams or needing a rapid reminder during a clinical attachment. Thoroughly updated, this new edition has been re-ordered by body systems with key surgical presentations ordered alphabetically within each section for ease of reference. Now with important new topics including bariatric surgery, endovascular techniques, nutrition, SIRS and sepsis, Rapid Surgery presents up-to-date knowledge succinctly for easy and rapid access to information.